Kaombo: Prosesi Upacara Pingitan Dan Gejala Perubahannya Dalam Kehidupan Masyarakat Desa Lasori Kabupaten Buton Tengah - Ayu, Lilis; Abdullah, Asran; Muak Hara, Kuflia (LeRIn - Universitas Dayanu Ikhsanuddin - Prodi. Sosiologi, 2025)
This study aims to explore the stages of the Kaombo ritual (female seclusion rite) as practiced by its participants, as well as to examine the emerging patterns of change in the performance of the Kaombo ceremony within the social life of the Lasori Village community in Central Buton Regency. Employing a qualitative approach with a descriptive-analytical method, the study collected data through interviews, observation, and documentation. The informants included traditional leaders or religious figures, bhisa (ritual guides), ritual actors, and participants of Kaombo. The findings indicate that the Kaombo ritual in Lasori Village consists of three major stages: the preparatory phase, the execution phase, and the concluding phase. Moreover, the study identified significant changes in the conduct of the Kaombo ritual, which include alterations in the timing of the ceremony, modifications in traditional clothing, and the incorporation of modern elements into certain aspects of the ritual process. These transformations have led to a gradual shift in both the symbolic meaning and the structural form of the Kaombo ritual, reflecting broader sociocultural changes within the community.